Management of distal unstable radius fractures with locking distal radius plates: a retrospective study - Sharma, Akash; Jain, Arpit; Luthra, Gaurav (International Journal of Research in Orthopaedics, 2022)
Background: Distal radius fractures that are unstable are challenging to treat. The locking distal radius plate screws is a superior alternative to the other forms of treatment (external fixator and K pin). The purpose of this study was to provide the radiographic and functional clinical outcomes of patients who had locking distal radius plate screws treatment. This study’s objective was to clinically assess the results of using a locking distal radius plate system to treat radius fractures. Methods: 31 patients with radius fractures are included in this retrospective clinical trial. They are all treated with a locking distal radius system made by Kaulmed Private Limited in Sonipat, Haryana, India. The patients were treated with variable angle locking distal radius plates that includes 2.4 mm KL-8 variable angle two column volar distal radius plates and 2.4 mm KL-8 variable angle volar rim distal radius plates. There were 31 patients consisting of 24 male and 07 female, with an average age of 44 years. The fractures were categorized based on AO classification and pre-operative fitness was assessed using American society of anaesthesiologist (ASA grade). The patients were assessed clinically, radiologically and functionally using visual analogue scale (VAS), post-operative radiographs and measuring grip strength and weight bearing respectively. Results: Surgery was performed on 31 patients with at-least three post-operative follow-up visits in 180 days. No patient in any group complained after the final follow up about any major complications or hardware problems, and every patient’s bone union was achieved successfully. Radiological outcomes also showed proper union in 6-7 weeks. Conclusions: Distal radius volar locking plates provide effective results in correcting distal radius anatomy.